2018
DOI: 10.26582/k.50.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Olympic and Paralympic Games Rio 2016

Abstract: The purpose of this study was to compare the athletes’ scores, penalties and efficiency between the Olympic and Paralympic Games Rio 2016, and identify which variable determined the winner of the matches. A total of 608 matches in the Olympic and Paralympic Games were analysed. Total relative scores (ippon, waza ari and yuko), penalties (shido per match) and efficiency were identified in the male and female categories, Olympic and Paralympic Games, and medallists and non-medallists. The main results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Most studies included both men and women ( n = 9); three and two investigations included only men and women, respectively, while the sex was not reported in another two studies. Half of the studies did not provide information on the sample distribution according to the degree of VI, while two investigations included sighted judokas 39,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies included both men and women ( n = 9); three and two investigations included only men and women, respectively, while the sex was not reported in another two studies. Half of the studies did not provide information on the sample distribution according to the degree of VI, while two investigations included sighted judokas 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…Two investigations included sighted judokas and found that they received more penalties, 40 and they also had a distinct advantage when fighting a blindfolded opponent 39 . A change in judo regulations resulted in shorter combats, according to the only investigation that focused on this subject 42 …”
Section: Resultsmentioning
confidence: 99%
“…This finding is contrary to earlier studies. Top judo athletes produced an effectiveness of 7.4% in 40 finals held between (Boguszewski, 2011a; 8.0±1.5% by male judokas in Rio 2016 (Kons et al, 2018); 8.7% by Olympic male champions of London 2012 8.7% in 150 matches organized between 20108.7% in 150 matches organized between -20128.7% in 150 matches organized between (Bocioaca, 2014; 8.9% by the World champion 2010 ; 11.9% by World champion 2015 (Pujszo et al, 2017); 17% in London 2012 (EJU, 2012);18.6% in World Championships 2011(Stankovic et al, 2015; and 28.4±4.2% by Olympic champions 2008 (Tabakov, 2009). The particular context of major sporting events, the status of athletes taking part in these competitions, and their level of technical-tactical preparations are among the factors affecting these efficiencies.…”
Section: Discussionmentioning
confidence: 96%
“…They analyzed temporal structure, technical variety, tactical choices, and other parameters of their accomplishment in high-level competitions (Table 1). Modeling the attack system is of interest only if the analysis covers several matches (Ait Ali Yahia, 2014;Kons et al, 2018;Ait Ali Yahia & Calmet, 2019;Ait Ali Yahia, 2020). To analyze only Olympic champions (Tabakov, 2009) or World champions Pujszo et al, 2017) is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are technical and tactical similarities between VI Judo and its Olympic counterpart, there is one key adaptation to the sport that alters the nature of competition. In VI judo, athletes must start the match with a two-handed grip on the jacket of the opponent already in place to decrease the visual demands of the sport (Gutiérrez-Santiago et al, 2011;Kons et al, 2018). This is in contrast to able-sighted judo, where athletes start the bout a few metres apart, after which they first must fight to engage and grip their opponent before they can attempt to throw him/her (Gutiérrez-Santiago et al, 2011).…”
Section: Introductionmentioning
confidence: 99%